Towards a corporate governance trust agent scoring model for collaborative virtual organisations. (8th June 2011) - French, Tim; Bessis, Nik; Xhafa, Fatos; Maple, Carsten
In this 'visionary' paper, we describe how a semiotic ladder, together with a supportive trust agent, can be used to address 'soft' trust issues in the context of collaborative Virtual Organisations (VOs). The intention is to offer all parties better support for trust (as reputation) management, including the reduction of risk and improved reliability of VO e-services. The semiotic ladder is intended to support the VO e-service life cycle through the articulation of e-trust at various levels of system abstraction, including trust as a measurable confidence level. A novel trust agent is used to provide the consumer with an objective measure of the trustworthiness of the e-service at runtime, just prior to its actual consumption. Specifically, VO consumer confidence level is informed via a set of Corporate Governance (CG) scores, which are used as a trust proxy for the 'real' owner of the VO.